Penerapan Prinsip Good Faith Dalam Perjanjian Pendahuluan Pada Perjanjian Pengikatan Jual Beli Tanah Dan Bangunan - Gregorius Febrian Wijaya; Amad Sudiro (UNES Law Review, 2023)
An agreement is a written or oral agreement made by two or more parties, each of whom agrees to obey what is contained in the agreement. This research uses a normative juridical approach and analysis. The research findings and discussion involve aspects such as the protection of good faith parties, the principle of good faith in the execution of agreements, and the legal implications of PPJB. The research conclusion emphasizes the importance of good faith in sale and purchase transactions, the need for legal protection for good faith parties, and the significant role of PPJB as a binding legal instrument. In the context of property sale and purchase, PPJB is perceived as an important means to protect the interests of the parties involved.